u-Button을 활용한 스마트 조명 제어시스템 - 최형도; 정인범; Choi, Hyeong-Do; Jung, In-Bum (한국정보통신학회논문지, 2013)
Everything has been simplified and abbreviated. The stream of times can be found through the smart phones since the ubiquitous world has be mentioned by Mark Webber. Judging by the flow of times, it's easy to predict that it will be more developed in the future. There are several ways of the development and one of them is to click a button in everything. For this study, the MaKey of MIT MELIALAB shows the possibility. As applying the study of clicking a button in everything, this paper proposes the Smart Lighting Control System using the u-Button. For the actual implementation, u-Button Module with MICAz and various sensors, Actuator Node composed of ZigBeX and LED Module are produced. 모든 것이 간소화되고 축약되는 시대가 도래하고 있다. 이것은 마크 웨버가 유비쿼터스 세상을 언급한 이래로 현재는 스마트폰을 통해 시대의 흐름을 살펴볼 수 있다. 이러한 시대의 흐름으로 미루어 볼 때, 미래에는 더 발전된 형태로 진화할 것이라고 예측할 수 있다. 그 진화방향은 여러 가지가 있지만, 그 중 하나는 모든 것을 버튼화 시키는 것이다. 이에 대한 연구로 MIT MEDIALAB의 MaKey는 그 가능성을 보여준다. 본 연구는 이러한 모든 것을 버튼화 시키는 연구의 응용으로 u-Button을 활용한 스마트 조명 제어 시스템을 제안한다. 실제 구현을 위해 MICAz와 각종 센서로 구성된 버튼역할의 u-Button모듈과 LED모듈 ZigBeX로 이루어진 Actuator Node를 제작하였다.